Respiratory manifestations of eosinophilic granulomatosis with polyangiitis (Churg–Strauss). Issue 5 (1st September 2016) - Cottin, Vincent; Bel, Elisabeth; Bottero, Paolo; Dalhoff, Klaus; Humbert, Marc; Lazor, Romain; Sinico, Renato A.; Sivasothy, Pasupathy; Wechsler, Michael E.; Groh, Matthieu; Marchand-Adam, Sylvain; Khouatra, Chahéra; et al.
The respiratory manifestations of eosinophilic granulomatosis with polyangiitis (EGPA) have not been studied in detail. In this retrospective multicentre study, EGPA was defined by asthma, eosinophilia and at least one new onset extra-bronchopulmonary organ manifestation of disease. The study population included 157 patients (mean±sd age 49.4±14.1 years), with a mean±sd blood eosinophil count of 7.4±6.4×10 9 L −1 at diagnosis. There was a mean±sd of 11.8±18.2 years from the onset of asthma to the diagnosis of EGPA, of 1.4±8.4 years from the first onset of peripheral eosinophilia to the diagnosis of EGPA, and of 7.4±6.4 years from EGPA diagnosis to the final visit. Despite inhaled and oral corticosteroid treatment, the severity of asthma increased 3–6 months before the onset of the systemic manifestations. Asthma was severe in 57%, 48%, and 56% of patients at diagnosis, at 3 years, and at the final visit, respectively. Persistent airflow obstruction was present in 38%, 30%, and 46% at diagnosis, at 3 years, and at the final visit, respectively. In EGPA, asthma is severe, antedates systemic manifestations by a mean of 12 years, and progresses to long-term persistent airflow obstruction despite corticosteroids in a large proportion of patients, which affects long-term management and morbidity. In EGPA, asthma is severe and progresses to persistent airflow obstruction despite corticosteroids in many patients http://ow.ly/8uf8301KSoT